Expressionisme I. - Verhegghe, Willie; Hof ter Nederloo, Sint-Pieters-Leeuw; BBL (Bank Brussel Lambert) Brussel (Sint-Pieters-Leeuw : De Vrienden van Nederloo, 1987)
Bervoets, Fred ; Burssens, Jan ; De Bruyne, Dees ; Decaestecker, Lea ; Gentils, Frans ; Leclercq, Guy ; Minnaert, Frans ; Pas, Wilfried ; Szymkowicz, Charles ; Theys, Yvan ; Vandercam, Serge ; Van Nazareth, Herman
Expressionisme I, Hof ter Nederloo, Sint-Pieters-Leeuw, 27 februari - 29 maart 1987
boek